2014
DOI: 10.1002/phy2.264
|View full text |Cite
|
Sign up to set email alerts
|

ACE2 deficiency increases NADPH-mediated oxidative stress in the kidney

Abstract: Angiotensin‐converting enzyme 2 (ACE2) is highly expressed in the kidney and hydrolyzes angiotensin II (Ang II) to Ang(1–7). Since Ang II is a strong activator of oxidative stress, we reasoned that ACE2 could be involved in the regulation of renal oxidative stress by governing the levels of Ang II. We, therefore, assessed levels of oxidative stress in kidney cortex of ACE2 knockout and wild‐type littermate mice under baseline conditions. We found multiple markers of increased oxidative stress in ACE2KO mice. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 49 publications
5
43
0
Order By: Relevance
“…In a previous report, increased renal expression of Ang II in rats treated with HgCl 2 was noted . Increased levels of endogenous Ang II promote local tissue damage by several mechanisms, including oxidative stress (Wysocki et al 2014), mainly through activation of NADPH oxidase and increased formation of O À 2 (Toda et al 2007;Garrido & Griendling 2009;Harrison & Gongora 2009;Wysocki et al 2014). Since Losartan and Enalapril treatment diminished the high levels of renal O À 2 found in the present study, a role for induced NADPH oxidase mediated by Ang II could be expected.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…In a previous report, increased renal expression of Ang II in rats treated with HgCl 2 was noted . Increased levels of endogenous Ang II promote local tissue damage by several mechanisms, including oxidative stress (Wysocki et al 2014), mainly through activation of NADPH oxidase and increased formation of O À 2 (Toda et al 2007;Garrido & Griendling 2009;Harrison & Gongora 2009;Wysocki et al 2014). Since Losartan and Enalapril treatment diminished the high levels of renal O À 2 found in the present study, a role for induced NADPH oxidase mediated by Ang II could be expected.…”
Section: Discussionsupporting
confidence: 52%
“…Since Losartan and Enalapril treatment diminished the high levels of renal O À 2 found in the present study, a role for induced NADPH oxidase mediated by Ang II could be expected. Indeed, blocking of AT1 receptor by Losartan reduced NADPH oxidase activity in several experimental models (Toda et al 2007;Wysocki et al 2014). In conjunction with any enhanced O À 2 production caused by Ang II, HgCl 2 could concurrently be decreasing local superoxide dismutase (SOD) activity (Jo et al 2004), leading to overall increases in renal O À 2 content.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wysocki et al. (30) demonstrated that the genetic ablation of ACE2 in mice was associated with increased kidney ROS owing to elevated levels of NADPH oxidase activity. Other studies demonstrated that both apoptosis and oxidative stress, two processes that are associated with I/R and are influenced by Ang II, were exacerbated by the loss of the Ace2 gene (31,32) and that repetitive episodes of hypoxia/reoxygenation that are associated with the transient cessation of breathing during sleep in OSA resemble I/R injury (33).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, ACE2 deficient mice have shown exacerbated NOX activity in the kidney and Ang-(1-7) treatment has presented inhibitory effects on ROS formation via the attenuation of NOX function [122].…”
Section: Ang Ii-stimulated Ros Generation In Liver Diseasementioning
confidence: 99%